2004
DOI: 10.1021/np040059+
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids from Brazilian Ilex Species and Their in Vitro Antitrypanosomal Activity

Abstract: From the leaves of Ilex affinis and Ilex buxifolia, two adulterant species of "erva mate" (Ilex paraguariensis), three new triterpenoid glycosides were isolated. Affinoside 1 (3beta-O-[beta-D-glucopyranosyl-(1-->3)-[2-O-acetyl-(1-->2]]-alpha-L-arabinopyranosyl pomolic acid 28-O-beta-D-glucopyranosyl ester, 1) was isolated from I. affinis, while buxifolioside I (28-O-beta-D-glucopyranosyl ester of (20S)-3alpha,19alpha-dihydroxyurs-12-ene-23,28-dioic acid, 7) and buxifolioside II (28-O-beta-D-glucopyranosyl este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 16 publications
1
23
1
1
Order By: Relevance
“…These compounds have previously shown an activity on Tbb with IC 50 = 2.9 g/ml with SI of 20.6 for oleanolic acid and IC 50 = 1.1 g/ml with SI of 6.0 for ursolic acid (Hoet et al, 2007). Others studies showed antitrypanosomal activity with IC 50 = 8.8 g/ml on Tbb and Trypanosoma brucei congolense for ursolic acid (Taketa et al, 2004) and an in vivo significant reduction of parasites of 75.7% at 2 mg/kg/d intraperitoneally during 13 days (Cunha et al, 2006). At a concentration of 20 mg/kg/d intraperitoneally during 20 days, reductions of parasitaemia of 60% for ursolic acid and 40% for oleanolic acid were observed (Ferreira et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…These compounds have previously shown an activity on Tbb with IC 50 = 2.9 g/ml with SI of 20.6 for oleanolic acid and IC 50 = 1.1 g/ml with SI of 6.0 for ursolic acid (Hoet et al, 2007). Others studies showed antitrypanosomal activity with IC 50 = 8.8 g/ml on Tbb and Trypanosoma brucei congolense for ursolic acid (Taketa et al, 2004) and an in vivo significant reduction of parasites of 75.7% at 2 mg/kg/d intraperitoneally during 13 days (Cunha et al, 2006). At a concentration of 20 mg/kg/d intraperitoneally during 20 days, reductions of parasitaemia of 60% for ursolic acid and 40% for oleanolic acid were observed (Ferreira et al, 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Topical use of Ilex paraguariensis extract could be then an alternative antifungal agent used for this infection. Triterpenoids from Ilex paraguariensis display inhibitory activities against Trypanosoma Cruzi (Taketa et al, 2004) Angiogenesis plays a key role in inflammation and repair as well as in cancer biology. Treatments performed with aqueous extract of maté and caffeine in the vascular membranes of chick embryos yolk sac revealed pro-vasculo-and angiogenic properties as well as embryonic growth enhancement (Strassmann et al, 2008).…”
Section: Effects Of Ilex Paraguariensis Extracts On Inflammationmentioning
confidence: 99%
“…Saponins have been reported to provide a hypocholesteremic effect by inhibiting the passive diffusion of colic acid through the formation of micelles preventing absorption, anticancer, antiparasitic (Taketa et al, 2004a;2004b), and anti-inflammatory properties.…”
Section: Primary Chemical Composition Of Yerba Matementioning
confidence: 99%